Adult neurobehavioral alterations in male and female mice following developmental exposure to paracetamol (acetaminophen): characterization of a critical period. Issue 10 (27th April 2017) - Philippot, Gaëtan; Gordh, Torsten; Fredriksson, Anders; Viberg, Henrik
Abstract: Paracetamol (acetaminophen) is a widely used non‐prescription drug with analgesic and antipyretic properties. Among pregnant women and young children, paracetamol is one of the most frequently used drugs and is considered the first‐choice treatment for pain and/or fever. Recent findings in both human and animal studies have shown associations between paracetamol intake during brain development and adverse behavioral outcomes later in life. The present study was undertaken to investigate if the induction of these effects depend on when the exposure occurs during a critical period of brain development and if male and female mice are equally affected. Mice of both sexes were exposed to two doses of paracetamol (30 + 30 mg kg –1, 4 h apart) on postnatal days (PND) 3, 10 or 19. Spontaneous behavior, when introduced to a new home environment, was observed at the age of 2 months. We show that adverse effects on adult behavior and cognitive function occurred in both male and female mice exposed to paracetamol on PND 3 and 10, but not when exposed on PND 19. These neurodevelopmental time points in mice correspond to the beginning of the third trimester of pregnancy and the time around birth in humans, supporting existing human data. Considering that paracetamol is the first choice treatment for pain and/or fever during pregnancy and early life, these results may be of great importance for future research and, ultimately, for clinical practice. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Developmental exposure to paracetamol has reached increased attention over the past years due to its possible link to adverse behavioral outcomes later in life. This study investigates if the induction of these effects depends on when the exposure occurs during a critical period of brain development and if male and female mice are equally affected. We showed that exposure on postnatal days 3 and 10, but not 19, affected adult cognitive performance, effects that are induced in both male and females.